The Impact of Online Customer Reviews on Enhancing Consumer Satisfaction - Roro Arinda Reswanti (CV. Publikasi Indonesia, 2024)
The development of digital technology has changed the way businesses interact with consumers, especially through online customer reviews. These reviews are an important element in the consumer decision-making process by providing social proof that strengthens the perception of the product or service. This study aims to analyze the influence of online customer reviews on consumer satisfaction in the culinary MSME sector in the city of Bandung. The research method uses a descriptive quantitative approach with a purposive sampling technique involving 150 active respondents on social media. Data was collected through a questionnaire with the Likert scale. The results of the validity and reliability test show that the research instrument meets quantitative research standards. Correlation analysis showed a positive and significant relationship between online customer reviews and consumer satisfaction with a correlation coefficient of 0.569. Positive reviews increase consumer confidence, while negative reviews decrease buying interest although the impact can be minimized through quick and professional responses from sellers. In conclusion, online customer reviews play an important role in creating consumer satisfaction, so companies need to manage these reviews effectively to maintain customer loyalty in the digital age.